Managerial accounting - Hilton, Ronald W. (Boston, MA : Irwin/McGraw-Hill, 1999)
The emphasis of this title is on teaching students to use accounting information in managing an organization. Students learn about the issues facing service, nonprofit, retail and manufacturing firms and about the managerial practices that the businesses use.
Includes index.
oif 27/03/15
Loan
Keywords: Managerial accounting